Sistemas agroflorestais urbanos: uma proposta de infraestrutura verde para uma urbanização agroecológica - D'Angelis, Gilberto Machel Veiga (Universidade Federal de São Carlos, 2023)
The increase of green areas in cities brings numerous social, environmental, and economic benefits, both in its productive aspects (as in the movements of vegetable gardens and urban agriculture) and concerning the ecosystem services that can be added to the creation or expansion of urban forests (carbon sequestration, improvement of the microclimate, reduction of pollution, integration of people with the environment, leisure). However, a proposal aggregating all these benefits simultaneously, systemically, and integrated into the urban landscape is stillchallenging. Thus, based on the integrating concept of Continuous Productive Urban Landscapes (derived from architecture) combined with the concept of Urban Food Forestry, this research set out to investigate (through a broad critical review of the literature) the use of Agroforestry Systems (AFS) as a strategy to compose productive landscapes and integrate – at the same time – the promotion of numerous ecosystem services to the urban design of cities. The results indicate that Agroforestry Systems can be seen as a new and promising typology of Green Infrastructure (GI) to support projects of cities in transition to agroecological urbanization or to project cities of the future in which urban ecosystems are connected from the outset to natural ecosystems and can thus co-evolve and develop in a symbiotic and beneficial to the surrounding nature.
Urban agroforestry systems: a proposal of green infrastructure for an agroecological urbanization
Systèmes agroforestiers urbains: une proposition d'infrastructure verte pour une urbanisation agroécologique
Keywords: Sistemas Agroflorestais (SAFs); Agrofloresta Urbana; Paisagens Urbanas Produtivas Contínuas (CPULs); Florestas Urbanas de Alimento (UFFs); Serviços Ecossistêmicos (SE); Infraestruturas Verdes (IV); Indicadores Agroflorestais; Agroforestry Systems (AFS); Urban Agroforestry (UAF); Continuous Productive Urban Landscapes (CPULs); Urban Food Forestry (UFFs); Ecosystem Services (ES); Green Infrastructure (GI); Agroforestry Indicators; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA::FLORICULTURA, PARQUES E JARDINS; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PAISAGISMO; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PROJETO DE ARQUITETUTA E URBANISMO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; CIENCIAS AGRARIAS; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO; CIENCIAS SOCIAIS APLICADAS::ECONOMIA; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::HIDROLOGIA FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA REGIONAL E URBANA::ECONOMIA URBANA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA AGRARIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA DOS RECURSOS NATURAIS; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE AGUA E SOLO; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE AGUA E SOLO::CONSERVACAO DE SOLO E AGUA; CIENCIAS AGRARIAS::AGRONOMIA::FLORICULTURA, PARQUES E JARDINS::ARBORIZACAO DE VIAS PUBLICAS; CIENCIAS AGRARIAS::AGRONOMIA::FLORICULTURA, PARQUES E JARDINS::PARQUES E JARDINS; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA URBANA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL::ADMINISTRACAO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL::DENDROMETRIA E INVENTARIO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL::ECONOMIA FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL::POLITICA E LEGISLACAO FLORESTAL; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PAISAGISMO::PROJETOS DE ESPACOS LIVRES URBANOS; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PROJETO DE ARQUITETUTA E URBANISMO::PLANEJAMENTO E PROJETO DO ESPACO URBANO; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::MANEJO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::TECNICAS E OPERACOES FLORESTAIS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::TECNOLOGIA E UTILIZACAO DE PRODUTOS FLORESTAIS; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::CONTROLE DE ENCHENTES E DE BARRAGENS; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::PLANEJAMENTO INTEGRADO DOS RECURSOS HIDRICOS; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::ECOLOGIA APLICADA A ENGENHARIA SANITARIA; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::QUALIDADE DO AR, DAS AGUAS E DO SOLO; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::DRENAGEM URBANA DE AGUAS PLUVIAIS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ADMINISTRACAO MUNICIPAL E URBANA; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ASPECTOS ECONOMICOS DO PLANEJAMENTO URBANO E REGIONAL; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ASPECTOS FISICO-AMBIENTAIS DO PLANEJAMENTO URBANO E REGIONAL; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ASPECTOS SOCIAIS DO PLANEJAMENTO URBANO E REGIONAL; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::INFRA-ESTRUTURAS URBANAS E REGIONAIS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::LEGISLACAO URBANA E REGIONAL; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::SERVICOS COMUNITARIOS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA::DENDROLOGIA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA::FLORESTAMENTO E REFLORESTAMENTO; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA::NUTRICAO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA::PROTECAO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA::SEMENTES FLORESTAIS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA::SOLOS FLORESTAIS; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA URBANA; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::TECNICAS E OPERACOES FLORESTAIS::EXPLORACAO FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::TECNOLOGIA E UTILIZACAO DE PRODUTOS FLORESTAIS::ANATOMIA E IDENTIFICACAO DE PRODUTOS FLORESTAIS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::TECNOLOGIA E UTILIZACAO DE PRODUTOS FLORESTAIS::QUIMICA DA MADEIRA